Effects of Hyperthyroidism on the Rectus Muscles in Mice - Nien, Chyong Jy; Jester, James; Bose, Swaraj (Frontiers in Neurology, 2010)
Background: Structural details of vertebrate extraocular muscles (EOMs) have shown an anatomically and functionally distinct laminar organization into an outer orbital (OL) and an inner global layer (GL). Since hyperthyroidism alters tissue oxidative metabolism through mitochondrial enzymes, it is expected that structural/mitochondrial changes may be seen in hyperthyroid EOMs. We investigated the alterations in the laminar organization and mitochondrial changes in hyperthyroid mouse EOMs. Methods: Hyperthyroidism was induced in C57BL/6 mice and fresh rectus muscles were obtained to identify functional mitochondria using MitoTracker® Green and confocal microscopy; frozen sections from rectus muscles were stained with anti-rabbit Troponin T (selectively present in the OL) to demonstrate changes in the OL and GL of the EOMs. Ultrastructural features of EOMs were studied using transmission electron microscopy (TEM). Results: Of all 4 rectus EOMs studied, the maximum change was seen in the inferior rectus muscle (IR) followed by medial rectus (MR). Myofiber cross sectional area measurements and Troponin T staining in the control IR EOMs demonstrated a smaller OL (113.2 ± 3.66 μm2 ) and higher density staining with Troponin T (90%) and a larger GL (411 ± 13.84 μm2 ) with low intensity staining (10%), while hyperthyroidism resulted in an increased OL (205.9 ± 5.3 μm2 ) and decreased GL (271.7 ± 7.5 μm2 ) p=0.001. Confocal microscopy demonstrated an intense staining especially in the outer rims in the hyperthyroid IR which was confirmed by TEM showing structural alterations in the mitochondria and a subsarcolemmal migration. Conclusions: The outer, thinner, orbital layer (OL) of the mouse EOM contains smaller diameter myofibers and fewer mitochondria while the inner, larger global layer (GL) contains larger diameter myofibers and larger density of mitochondria. Hyperthyroidism results in a significant alteration in the laminar organization and mitochondria of mouse EOMs.